Farmers' Behavior in Utilization Sources of Shallot Agribusiness Information (Allium ascalonicum) - Adittiyan, Heru; Nurhadiatna, Taufik; Arif, Yusuf Islahudin; Faqih, Achmad (Green Publisher Indonesia, 2023)
-